Case study : demolition practice of old MARA building on Lot 1767, Lot 1218 and Pt 4, Section 46, mukim Bandar Kuala Lumpur, Jalan Tuanku Abdul Rahman. - Khairul Faiq, Selaiman (2006)
Nowadays, there are various types of procedure or provision issued by many institutions and departments all over the world such as British Standard Institution, Occupational Safety and Health Act, Department of Environment, etc. in order to provide the guideline for good practice and guidance in demolition works. The research contains basic information of procedures, process, techniques and demolition methods, legislative requirement and example of demolition project in this country. It also includes the latest requirement for practitioners on better planning and helps them to select the most suitable demolition method. This research should be used in conjunction with Verified Regulations to develop the work plan for approval by Public Work Department (JKR), Local Authority etc. This study also proposed the procedure on how the work plan is developed. . It is essential to produce the work plan to ensure a systematic and consistent decision can be produced before execution. Beside, a study about demolition work of old MARA building on Lot 1767, Lot 1218 and PT4, section 46, Kuala Lumpur, Jalan Tuanku Abdul Rahman had been conducted to be a guideline in the process of work planning also as an example of legislative requirement needed by local authorities of this country and helping in verification process.